The relationship between unilateral and bilateral jump kinematics and sprint performance - McCurdy, K.; Walker, J.; Guerrero, M.; Kutz, M. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to determine the relationship between measures of unilateral and bilateral jumping performance and 10- and 25-meter sprint performance. Methods: Fifteen division I women soccer players (height 165 +/- 2.44 cm, mass 61.65 +/- U kg, age 20.19 +/- 0.91 yrs) volunteered to participate in this study. After a 10-minute warm up and dynamic stretches, the subjects completed a 10-meter and 25-meter sprint test. Sprint time was measured with an accelerometer using an electronic timing gate system (Inform Sport Training Systems, Victoria, BC. Canada). The accelerometer was worn at the waist, which also measured step length, step frequency and jump kinematics. The following jump kinematic variables were measured: vertical jump height, horizontal jump distance, total contact time (eccentric through concentric time), concentric contact time, and flight time. Two trials at each sprint distance were completed with 2 minutes of rest between each trial while the best time was recorded for analysis. After a minimum of 48 hours of rest, the subjects completed the jump tests. After a 10-minute warm up and dynamic stretches, the following jumps were completed in random order with a 1-minute rest period between each trial: bilateral countermovement vertical jump (BCV), bilateral counter movement horizontal jump (BCH), bilateral 40 cm drop vertical jump (BDV), bilateral 40 cm drop horizontal jump (BDH), unilateral countermovement vertical jump (UCV), unilateral countermovement horizontal jump (UCH), unilateral 20 cm drop vertical jump (UDV), and unilateral 20 cm drop horizontal jump (UDH).The unilateral jumps were performed on each leg. The trial with the best reactive strength (RS) (jump height or distance/total contact time) was recorded to analyze the relationship between jump kinematics and sprint performance. The relationship between the best flight time to concentric contact time ratio (FT/CCT) and sprint performance was also analyzed. Results: None of the bilateral jump kinematics significantly correlated with 10 m and 25 m sprint time, step length, or step frequency. However, RS significantly correlated with 25 m step length during the left leg UCV (r = 0.63, p = 0.02, SEE = 0.057 m). Right leg jump height (r = -0.71, p = 0.006, SEE = 0.152 s), RS (r = -0.67, p = 0.012, SEE = 0.161 s), and FT/CCT (r = -0.58, p = 0.04, SEE = 0.176 s) were significantly correlated with the 25 m sprint time during the UCV. Right leg FT/CCT was also significantly related to 25 m step length (r = 0.68, p = 0.03, SEE = 0.06 m) during the UDV. Conclusion: In comparison to bilateral jumps, unilateral vertical jumps produced a stronger relationship with sprint performance. Practical Application: The data indicate that greater emphasis on unilateral jump training may produce better improvement in sprint performance than bilateral training.